GWAS of resistance to three bacterial diseases in the Andean common bean diversity panel - Soler-Garzón, Alvaro; Mulube, Mwiinga; Kamfwa, Kelvin; Lungu, Davies M.; Hamabwe, Swivia; Roy, Jayanta; Salegua, Venâncio; Fourie, Deidré; Porch, Timothy G.; McClean, Phillip E.; Miklas, Phillip N. (Frontiers in Plant Science, 2024)
Bacterial brown spot (BBS), caused by Pseudomonas syringae pv. syringae (Pss), common bacterial blight (CBB), caused by Xanthomonas axonopodis pv. phaseoli (Xap) and Xanthomonas fuscans subsp. fuscans (Xff), and halo bacterial blight (HBB), caused by Pseudomonas syringae pv. phaseolicola (Psph), are major bacterial diseases thatwhich severely impact common bean yields, affecting global food security. Andean-origin dry beans, representing large-seeded market classes, are particularly susceptible. Using 140,325 SNPs, a multi-locus GWAS was conducted on subsets of the Andean diversity panel (ADP) phenotyped for BBS in South Africa; CBB in Puerto Rico, South Africa, and Zambia; and HBB in South Africa, through natural infection, artificial inoculation, or both. Twenty-four QTL associated with resistance were identified: nine QTL for BBS, eight for CBB, and seven for HBB. Four QTL intervals on Pv01, Pv03, Pv05, and Pv08 possessed overlapping BBS and HBB resistance. A genomic interval on Pv01, near the fin gene, which conditions determinate growth habit, was linked to resistance to all three pathogens. Different QTL were detected for BBS and CBB resistance when phenotyped under natural infection versus artificial inoculations. These results underscore the importance of combining both phenotyping methods in multi-GWAS to capture the full genetic spectrum. Previously recognized CBB resistance QTL SAP6 and SU91 and HBB resistance QTL, HB4.2, and HB5.1, were observed. Other common (MAF >0.25) and rare (MAF <0.05) resistance QTL were also detected. Overall, these findings enhance the understanding and utilization of the bacterial resistance present in the ADP for developing common beans with improved resistance.